The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2495/sdp130051
|View full text |Cite
|
Sign up to set email alerts
|

The leverage of corporate environmental protection concepts on employee motivation

Abstract: Corporate environmental protection is nowadays no longer just a marketing tool or an annoying necessity for a good reputation, but for many companies an integrated element of the corporate culture and of doing business. In a case study of a company in Austria, this paper investigates a feasible additional advantage for corporate environmental protection in terms of a positive leverage on employee motivation. After giving an overview of the most important theoretical approaches and tools regarding corporate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…More recent studies have shown that the employees are in general interested in developing a sustainable economic and social environment [36,37]. Bastien and Hung [38] analyzed the connection between the sustainable development and the intrinsic and extrinsic motivation of the employees from a company which was following a long term policy of sustainability.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…More recent studies have shown that the employees are in general interested in developing a sustainable economic and social environment [36,37]. Bastien and Hung [38] analyzed the connection between the sustainable development and the intrinsic and extrinsic motivation of the employees from a company which was following a long term policy of sustainability.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%